PENGARUH SPIRITUAL LEADERSHIP TERHADAP KINERJA, ORGANIZATIONAL BASED SELF-ESTEEM SEBAGAI VARIABEL INTERVENING - Khafid, Abdul; Astuti, Fitria Yuni (Kinerja, 2023)
This study aims to analyze the role of Organizational Based Self Esteem (OBSE) in mediating the influence of Spiritual Leadership on the HR Performance of the Sun Life Syariah Insurance Agency team Al Fateeh Semarang. A sample of 102 employees. The sample selection method used in this study is purposive sampling method, namely sampling with techniques adapted to research objectives where the samples used have certain criteria determined based on their positions consisting of Agency Directors, Senior Agency Managers, Agency Managers and Financial Advisors. . The data collection method used in this study was by giving a questionnaire. Data analysis techniques This study uses the SEM-PLS analysis method. Organizational research results provide a positive and influential role in mediating the effect of Spiritual Leadership on Performance. Spiritual leadership influences performance. Organizational Based Self Esteem influences performance.